Comparative analysis between static compensator (STATCOM) and dynamic voltage restorer (DVR) for voltage SAG mitigation: article / Siti Azlina Abon - Abon, Siti Azlina (2011)
Voltage sags is the most common type of power quality disturbance in the distribution system. Voltage sag can be caused by abrupt increases in loads such as short circuits or faults, motor starting, or electric heater turn on, or caused by increase in source impedance, typically caused by a loose connection. Dynamic Voltage Restorer (DVR) and Static Compensator (STATCOM) is one of the mitigation techniques used to mitigate voltage sag. The main objective of this analysis is to compare the mitigation techniques between Static Compensator (STATCOM) and Dynamic Voltage Restorer (DVR) to determine the best technique to improve the voltage sags. Static Compensator (STATCOM) and Dynamic Voltage Restorer (DVR) is based on Voltage Source Converter (VSC) principle. The well developed graphic and facilities available in an industry standard power system package, namely PSCAD/EMTDC, are used to conduct all aspects of model implementation and to carry out the simulation studies. Both of the mitigation techniques will be tested on different type of fault which is three phase fault and double line to ground fault. The analysis will focus on the effectiveness of Static Compensator (STATCOM) and Dynamic Voltage Restorer (DVR) techniques in mitigating the voltage sags. And the study also investigates the effect of harmonic for different type of fault for each mitigation techniques. At the end of the project the Dynamic Voltage Restorer (DVR) is more effective to improve voltage sag than Static Compensator (STATCOM) whilst is the best solution for the effect of harmonic.